2008
DOI: 10.1016/j.ijimpeng.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of low-energy/low-velocity impact on Nomex honeycomb sandwich structures with metallic skins

Abstract: Abstract.In the aircraft industry, manufacturers have to decide quickly whether an impacted sandwich needs repairing or not. Certain computation tools exist at present but they are very time consuming and they also fail to perfectly model the physical phenomena involved in an impact. In a previous publication, the authors demonstrated the possibility of representing the NomexTM honeycomb core by a grid of nonlinear springs and have pointed out both the structural behaviour of the honeycomb and the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 29 publications
4
49
0
1
Order By: Relevance
“…In this region the crushing and fracture of the cores start ( Figure 5). Depending on the core densification at the end of Region 3, an increase in the compressive stress is observed, as was reported in [16][17][18][19][20][21][22][23][24] .…”
Section: Modeling Of the Cell Walls Of Honeycomb Compositessupporting
confidence: 69%
See 1 more Smart Citation
“…In this region the crushing and fracture of the cores start ( Figure 5). Depending on the core densification at the end of Region 3, an increase in the compressive stress is observed, as was reported in [16][17][18][19][20][21][22][23][24] .…”
Section: Modeling Of the Cell Walls Of Honeycomb Compositessupporting
confidence: 69%
“…They have determined that the critical buckling load of Nomex is higher than that of aluminum comb composite panels for all cell sizes. Castanié et al 17 showed that the compression load is essentially taken by the vertical edges of the hexagonal cell. From the axial compression collapse tests on the aluminum honeycomb sandwich panel specimen, various potential influential parameters, i.e., the core height, core-cell thickness and panel aspect ratio, it was observed that the core height would be a crucial parameter affecting the sandwich panel's ultimate compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the related literature, the main topic is clearly the compressive response, a phenomenon that has been studied for a long time (see McFarland since 1965 [12] or Wierzbicki [13]). Many authors have studied the compressive behavior -mainly to analyse the energy absorbing capabilities of honeycomb ( [12][13][14][15][16][17] for example) or, more precisely, the crush behavior of the core after a low-velocity/low-energy impact on a sandwich [17][18][19][20][21][22][23][24]. Today, the tendency is to use very refined finite element analysis with explicit code to model the complex failure mode following crushing of the Nomex Honeycomb core.…”
Section: Introductionmentioning
confidence: 99%
“…However, by understanding the structural behavior of the hexagonal cell and by making an analogy with the postbuckling of stiffened structures [22], it is possible to propose simplified discrete models that are very accurate [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…An accelerometer is sometimes placed on the impactor, but its use is restricted to low velocity impacts performed with drop weight devices [7] and the projectiles cannot be easily instrumented with an accelerometer in the context of medium velocity impacts obtained with gas-guns.…”
mentioning
confidence: 99%